Exploring the barriers and facilitators of nutrition and dietary intake among school-aged children in the urban low-income setting of Addis Ababa - Adugna, Yimer Mihretie; Ayelign, Abebe; Zerfu, Taddese Alemu (Korean Nutrition Society and the Korean Society of Community Nutrition, 2025)
BACKGROUND/OBJECTIVES Healthy eating supports mental clarity, physical development, and focus in the classroom. However, government policy, cultural customs, education, family income, and food access, influence children's nutrition, which in turn affects school-age children's growth, development, and academic achievement. This study aimed to explore the barriers and facilitators influencing the nutritional and dietary intake of school-age children in urban low-income settings in Addis Ababa, Ethiopia.